Case Report: Surgical challenges and insights in a child with a blunt left diaphragmatic and pericardial rupture and heart subluxation - Kassie, Melaku Tessema; Ayana, Motuma Gonfa; Abebe, Ruth Betremariam; Abebe, Befikadu Molalign (Frontiers in Surgery, 2024)
Introduction Blunt diaphragmatic rupture (BTDR) is a rare condition that can occur in children following high-energy blunt thoracoabdominal trauma. In less than 1% of the cases, pericardial rupture can coexist with a BTDR. A coexistence of BTDR and pericardial rupture can result in displacement of the heart and is associated with high mortality. Clinical presentation is non-specific and requires a high index of suspicion for early management. Case presentation A 4-year-old child presented to the emergency unit of our hospital following high-energy trauma with severe respiratory distress. Initially, a left-side chest tube was inserted, but it resulted in no clinical improvement. A chest x-ray showed a collapse of the left lung with a herniation of bowel loops into the left hemithorax. An exploratory laparotomy was done, which revealed a 10 cm × 4 cm defect in the left hemidiaphragm with a medial extension involving the pericardium. The fundus of the stomach and left lobe of the liver were displaced into the pericardial space, pushing the cardiac apex posteriorly to the right side. Concomitantly, the transverse colon and small bowel were displaced into the left pleural space. After the reduction of the herniated abdominal viscera back into the peritoneal cavity, the pericardial sac was repaired by employing an interrupted resorbable suture, while the diaphragmatic defect was repaired by using a horizontal mattress. No other injuries were identified and the abdomen was closed in layers. Conclusion BTDR with pericardial rupture is an elusive condition with a high mortality rate that necessitates a high index of clinical suspicion. Early surgical repair of the defect with a reduction of herniated organs can reduce morbidity and mortality.